2012
DOI: 10.1007/s00101-012-2086-1
|View full text |Cite
|
Sign up to set email alerts
|

Äußern Assistenzärzte und Pflegekräfte sicherheitsrelevante Bedenken?

Abstract: The authority gradient can have a major negative impact on perioperative patient care. Residents and nursing staff are seldom able to challenge the attending physicians when patient safety is at risk. However, even attending physicians who normally accept feedback and criticism from team members can fail to receive support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…St. Pierre et al conducted a full-scale simulation study in anesthesiology to observe speaking up behaviors. Nurses and residents challenged an attending in only few of the critical situations created by the attendant, including fatal drug administrations [6]. Speaking up behaviour of nurses has been associated with improved team performance of operating room teams in a simulation study [7].…”
Section: Introductionmentioning
confidence: 99%
“…St. Pierre et al conducted a full-scale simulation study in anesthesiology to observe speaking up behaviors. Nurses and residents challenged an attending in only few of the critical situations created by the attendant, including fatal drug administrations [6]. Speaking up behaviour of nurses has been associated with improved team performance of operating room teams in a simulation study [7].…”
Section: Introductionmentioning
confidence: 99%
“…Stern et al report from the medical field that, in rigid hierarchies, subordinate team members tend to keep their opinions or misgivings to themselves for fear of retribution, which can lead to treatment errors 17 ; a similar situation was found by St. Pierre et al who observed that foundation doctors/house officers/specialist registrars and nursing staff kept information relating to safety to themselves and away from the senior registrar because of a too steep hierarchy gradient. This was judged a risk factor for patient safety 18 . Doctors and nursing staff feel shame for their mistakes, for which reason they do not openly communicate about them 19 ; yet an open attitude to oneʼs own mistakes is crucial in identifying underlying causes and to avoid future errors.…”
Section: Discussionmentioning
confidence: 99%
“…In einer Cockpitstudie unter Militärpiloten zeigte sich, dass weniger unerwünschte Ereignisse auftraten, wenn der Rangunterschied zwischen dem Piloten und dem Kopiloten nicht zu groß war 16 . Stern et al berichten aus dem medizinischen Bereich, dass untergeordnete Teammitglieder in starren Hierarchien dazu neigen, ihre Meinung oder Vorbehalte aus Angst vor Strafe für sich zu behalten, was zu Behandlungsfehlern führen kann 17 ; Ähnliches findet sich bei St. Pierre et al, die beobachteten, dass Assistenzärzte und Pflegekräfte sicherheitsrelevante Informationen aufgrund eines zu steilen Hierarchiegefälles gegenüber dem Oberarzt für sich behielten, was als Risikofaktor für die Patientensicherheit gewertet wurde 18 . Ärzte wie Pflegekräfte neigen dazu, sich für Fehler zu schämen und sie daher nicht offen zu kommunizieren 19 ; dabei ist ein offener Umgang mit den eigenen Fehlern unabdingbar, um die zugrunde liegenden Ursachen zu identifizieren und zukünftige Fehler zu vermeiden.…”
Section: Diskussionunclassified
“…In a recently published simulation study only 28% of the staff members dared to contact their senior physician regarding their concerns about the safety of a planned measure while the other staff members remained silent hoping for a spontaneous solution of the conflict. In nearly 90% of the cases the silence led to the situation that a possibly lethal dose of a drug was given [42]. (Tab.…”
Section: Team Work and Patient Safetymentioning
confidence: 99%